Influence of Bean Flour (Phaseolus vulgaris) on Cardiac Remodeling after Acute Myocardial Infarction in Rats - Vieira, Nayane Maria [UNESP]; Monte, Marina Gaiato [UNESP]; Balin, Paola da Silva [UNESP]; Campos, Dijon Henrique Salomé de [UNESP]; Cabral Filho, Ronny Peterson [UNESP]; Fujimori, Anderson Seiji Soares [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Alonso, Diego Peres [UNESP]; Correa, Camila Renata [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; et al. (SAGE Publications, 2025)
Despite the introduction of new drugs, cardiac remodeling (CR) following myocardial infarction (MI) is still associated with increased mortality. Therefore, the search for new therapeutic strategies and bioactive compounds capable of attenuating CR is highly relevant. Although the underlying mechanisms are not fully understood, growing evidence suggests that oxidative stress regulation and modulation of the intestinal microbiota may contribute to the cardioprotective effects of bean consumption in cardiovascular diseases. We investigated the influence of bean flour on CR and intestinal microbiota after MI. Male Wistar rats underwent experimental infarction or sham surgery and were allocated into (1) Sham fed a standard diet (C = 18); (2) MI fed a standard diet (I = 22); and (3) MI fed a diet with bean flour (IB = 28) 15%. After 3 months were submitted to functional, morphometric, and biochemical study. The average infarct size was 38% for the I group and 40% for the IB group, there being no difference between the groups. The MI groups presented morphological changes and functional variables compared with C. Beans did not attenuate these changes, however, microbiota, the S24-7 Bacteroides, and the Halobacteriaceae firmicutes had reduced abundance after the MI in IB group. The supplementation of bean flour modulates the intestinal microbiota after MI. However, it does not attenuate the CR process following MI.